Pengembangan Digi Ecosmart, Ekosistem Ekonomi Digital Cerdas Berbasis Immersive Technology PT Nuswantoro Informasi Teknologi - Denny Trias Utomo; Mochammad Rifki Ulil Albaab; Ahmad Fahriyannur Rosyady; Adi Sucipto; Sholihah Ayu Wulandari (Universitas Nurul Jadid, 2023)
Sidoarjo Regency is a Delta Plain with an altitude between 0 to 25 m, a height of 0-3m with an area of 19,006 Ha, covering 29.99%, is a fishpond area located in the eastern part of the Central Region which has fresh water with an altitude of 3-10 meters above sea level is a residential area, trade and government. Covering 40.81%. The western region with an altitude of 10-25 meters above sea level is an agricultural area. [1],[2]The Matching Fund Program is a program funded by the Ministry of Education and Culture, Ministry of Research and Technology to strengthen cooperation between PTs and DUDI to jointly form the Merdeka Learning Ecosystem - Merdeka Campus. At the end of the program, a better and sustainable working relationship will be established between PT and DUDI, which is expected to contribute to solving real problems in the field or carrying out national strategic actions. [3]The method used on this project is prototyping, which is a system development method in which prototypes are built, tested and then reworked as necessary until acceptable results are achieved of the system or a complete product can be developed.